Biolarvacide of Culex quinquefasciatus - Rian Oktiansyah; Anggun Wicaksono; Fahmy Armanda; Amin Nurokhman; Ummi Hiras Habisukan; Kurratul ‘Aini; Yustina Hapida (Biota, 2020)
Biolarvicide is the larvicide derived from plants and relatively safe. The objective of this study was to determine the effect of pletekan leaf powder (Ruellia tuberosa), mimosa (Mimosa pudica), papaya (Carica papaya), and guava (Psidium guajava) on Culex quiquefasciatus larval mortality. The method was an experimental with a completely randomized design consisted of 5 treatments (0 gr, 0,25 gr, 0,5 gr, 0,75 gr, and 1 gr) and 5 repetitions for each plant. The data were analyzed by analysis of variance. Based on the results, leaf powder used in the study, namely guava leaves powder (1 gr), mimosa (1 gr), leaves of pletekan (1 gr), and leaves of papaya (1 gr) showed a very significant effect (P < 0,05) on Culex quiquefasciatus larval mortality. It can be concluded that the pletekan, mimosa, papaya, and guava had the potential as biolarvicide of Culex quinquefasciatus.